Transformasi Pembelajaran Dual Track System Di Pondok Pesantren Mangunsari Nganjuk Perspektif Kurt Lewin - Aulia Dini Afifatusholihah; Binti Fikhratin; Lucky Ilham Prayoga; Syafiq Al Faizar (Sekolah Tinggi Islam Kendal, 2026)
Salaf pesantren are confronted with the challenges of the modern era, which require the integration of traditional religious education and formal schooling in order to remain relevant to contemporary demands. This study aims to describe and analyze the process of learning transformation at Pondok Pesantren Mangunsari Nganjuk from the perspective of Kurt Lewin’s theory of change, as well as to identify the supporting and inhibiting factors influencing this process. Employing a qualitative research design with a case study approach, the findings reveal that Pondok Pesantren Mangunsari has successfully transformed from a purely salaf system into a dual-track education model by integrating a formal Madrasah Tsanawiyah (MTs) into its educational structure. This transformation aligns with the three stages of Kurt Lewin’s change theory: unfreezing (the emergence of awareness of the need for change), changing (the implementation of innovation through the establishment of the MTs), and refreezing (the institutionalization of the new system through sustainable policies and the formation of a new learning culture). The main inhibiting factor identified is the issue of leadership succession, while a crucial supporting factor is the successful development of a new, loyal, and innovation-oriented community base through Jam'iyah Istighotsah. The study concludes that pesantren are capable of strategically synthesizing tradition and modernity to respond to contemporary challenges without losing their fundamental identity.